(untitled) (Scientific journal of the Fergana State University, 2023)
In the article, the contribution of Shuhrat, the national writer of Uzbekistan, to the development of our poetry is explained as an ehample of the analysis of several centuries. The ability of the poet to create lyrical pictures with the effective use of pictorial expressions and tools will be shown. Philosophical expression, popular melody, consistent imagery, saturation with delicate experiences are important aspects that ensure the impressive and attractiveness of Shuhrat’s poetry.